Chromatographic and Spectrophotometric Analysis of Endosulfan in Vegetables - El Hassan, Khaled Mohamed (Journal of agricultural, environmental and veterinary sciences, 2018)
A High Pressure Liquid Chromatography (HPLC) and Spectrocopic methodologies have been validated for the determination of α Endosulfan, β Endosulfan and Endosulfan Sulphate in tomato “Lycopersicon esculentum Mill”. The chromatographic separation method was based on Liquid-Liquid Extraction (LLE) using two immiscible solvents. Acetonitrile/water mixture (70/30, v/v %) was used as a mobile phase. The HPLC was equipped with UV/visible detector, the separation was achieved on μ-Bondapak C18 column with dimensions, 4. 0 x 125 mm and 5-micron particle diameters using activated florisil to remove the interferences from the extract. The chromatographic experiments were carried out in triplicate at three fortifications levels 1, 2 and 3 Part per Million (ppm). HPLC’s detector was linear for the determination of pesticides with Correlation Cofficient (r) values < 0. 99. The Limit of Detection (LOD) values was 0. 020071, 0. 002352 and 0. 01619 ng/ml. The Limit of Quantification (LOQ) values were 0. 066903, 0. 0078414 and 0. 05396 ng/ml. The Recoveries percentage (R) of the pesticides studied ranged from 88. 13% to 98. 77%, 84. 60% to 96. 86% and 82. 90% to94. 85% and the Coefficient of Variation (CV) values ranged from 0. 003 to 0. 005, 0. 005 to 0. 0057 and 0. 004 to 0. 007 for α Endosulfan, β Endosulfan and Endosulfan Sulphate, respectively. The spectrophotometric method was based on the liberation of sulphur dioxide after addition of alcoholic potassium hydroxide, the liberated sulpher dioxide was passed through hydrogen peroxide and diphenylamine and the light violet color of diphenyl benzidine was measured at 605 nm using spectrophotometer. The Spectrophotometric experiments were carried out in triplicate at three fortifications levels 3, 5 and 7 Part per Million (ppm). The spectrophotometer showed a linear response for the detection of pesticide with (r) value >0. 99. The Limit of Detection (LOD) value was 0. 089953ng/ml, the Limit of Quantification (LOQ) value was 0. 299843ng/ml. The Recoveries percentage (R) values ranged from 89. 23%to 99. 02% and the Coefficient of Variation (CV) values ranged from 0. 01407 to 0. 02820. The levels of Endosulfan recovered in both methodologies were above the Maximum Residue Level (MRL) of Endosulfan in tomato (0. 5 ppm).